Multimodality treatment of intracranial arteriovenous malformations in South Island, New Zealand. (March 2020) - Pal, S.; Nicholson, F.; Boet, R.; Laing, A.; Collecutt, W.; Lim, A.; Hitos, K.
Highlights: Retrospective review of brain AVMs treated with surgery, embolisation and radiotherapy. Patient selection is key to surgical resection outcomes. Onyx embolisation is a safe and effective treatment with acceptable morbidity and mortality. Multimodality treatment can achieve cure rates of 50%. Abstract: Treatment of intracranial arteriovenous malformations is complex and multidisciplinary. This article presents the treatment model utilized in Christchurch, New Zealand which provides cerebrovascular surgery and interventional neuroradiology to the entire south island (approximate population of 1.1 million). A total of 40 patients treated over a 10 year period (2004–2014) are analysed here. Nine patients were managed surgically and complete resection was achieved in 100% of cases. Permanent mortality was 0% and permanent morbidity was 22% however median mRS improved from 3.0 preoperatively to 1.0 at follow up. Embolisation was utilized in 31 patients (mean age 40), of which 45% presented with haemorrhage, 39% with seizures, 10% with a headache only, and 6% with a deficit. None were found incidentally. The Spetzler-Martin grade 1 cases accounted for 10% of the cohort, 23% were grade II, 42% grade III, 23% grade IV and 3% grade V. A single aneurysm was present in 42% of cases, and multiple in 13%. The nidus was obliterated in 9.6% of cases with a morbidity rate of 6.5% and mortality rate of 3%. Modified Rankin scale improved marginally from 0.9 at diagnosis to 0.88 at final follow up (mean 22 months). There were no cases of recanalization. The total nidus obliteration rate using our algorithm of surgery alone for small accessible lesions, then staged embolization for larger lesions with adjuvant radiosurgery reserved for cases with residual nidus, was 50%.